VD_FINDINFO Jug / 2018 / 152 vom 27. November 2017 - VD Tribunal cantonal (2017)
VOLDROIT PÉNAL, UTILISATION FRAUDULEUSE D'UN ORDINATEUR, PEINE PÉCUNIAIRE, AMENDE | 106 CP, 139 ch. 4 CP, 147 CP, 34 CP, 42 CP, 44 CP, 47 CP, 49 CP